Factors predicting Registered Nurses' intentions to leave their organization and profession: A job demands‐resources framework. (5th December 2017) - Moloney, Willoughby; Boxall, Peter; Parsons, Matthew; Cheung, Gordon
Abstract: Aims: To develop a comprehensive model of nursing turnover intention by examining the effects of job demands, job resources, personal demands and personal resources on burnout and work engagement and subsequently on the intention to leave the organization and profession. Background: The ageing population and a growing prevalence of multimorbidity are placing increasing strain on an ageing nursing workforce. Solutions that address the anticipated nursing shortage should focus on reducing burnout and enhancing the engagement of Registered Nurses (RNs) to improve retention. Design: A cross‐sectional survey design. Method: Data were collected in 2014–2015 via an e‐survey from 2, 876 RNs working in New Zealand. Data were analysed with structural equation modelling. Results: Higher engagement results in lower intention to leave the organization and profession. Burnout has significant effects on intentions to leave through lower engagement. While most of the demands and resources' variables (except professional development) have effects on intentions to leave, greater workload and greater work‐life interference result in higher burnout and are the strongest predictors of intentions to leave. Greater emotional demands (challenges) and greater self‐efficacy also have strong effects in lowering intentions to leave through higher engagement. Conclusions: Employee burnout and work engagement play an important role in transmitting the impacts of job demands, job resources, personal demands and personal resources into RN intention to leave the organization and profession. Work‐life interference and high workloads are major threats to nursing retention while challenge demands and higher levels of self‐efficacy support better retention.